DO REALLY COMPENSATION EFFECT ON PERFORMANCE COMMITMENTS: TAXI DRIVER ONLINE (G0-JEK) IN THE CITY OF JAMBI? - Sry Rosita; Fitri Widiastuti; Dian Mala Fithriani Aira (Management Department, Faculty of Economics and Business, Universitas Jambi, 2018)
This research aims to analyze the commitment online taxi driver (Go-Jek) based on the components of a commitment that is continuous, affective, normative, and analyze the effect of compensation on performance motorcycle taxi driver online as well as influence commitment, compensation on performance the driver's taxi online (Go-Jek) in the town of Jambi. This research was conducted in the city of Jambi and surrounding areas. The population in this research is the entire taxi driver online (Go-Jek) operating in the city of Jambi and the surrounding area. Sampling using a purposive sampling method. The research on using primary data. The main data needed is (1) data on organizational commitment (affective, continuous, and normative) drivers Go-Jek, (2) the compensation data drivers Go-Jek, (3) performance data Drivers Go-Jek. The primary data were obtained directly from the respondent. Data collection using a structured questionnaire, asked respondents to use a questionnaire. This research uses descriptive quantitative and regression analysis.